Pyrolysis of date seeds loaded with layered double hydroxide: Kinetics, thermodynamics, and pyrolytic gas properties. (15th January 2022) - Hai, Abdul; Bharath, G.; Ali, Imtiaz; Daud, Muhammad; Othman, Israa; Rambabu, K.; Haija, Mohammad Abu; Hasan, Shadi W.; Banat, Fawzi
Graphical abstract: Highlights: Date seeds are pyrolyzed in situ in a fluidized bed. Different forms of LDH are synthesized by the co-precipitation method. CoFe-LDH improves the quality of pyrolysis products i.e. bio-oil and gas. Increasing the conversion rate from 40% to 80% decreases the activation energy. Diffusion-control and reaction model are probable mechanisms of LDH-DS pyrolysis. Abstract: Development of date seeds in-situ pyrolysis utilizing layered double hydroxide (LDH)-based catalysts is still in its infancy. This study investigates the thermokinetics of date seeds (DS) loaded with LDH by thermogravimetric analysis. Three different LDHs, namely Mg-Fe (MF), Ni-Fe (NF), and Co-Fe (CF), were synthesized by the co-precipitation method and loaded with dried date seed powder in a 1:10 ratio, which were then pyrolyzed in-situ in a custom-designed pyrolytic reactor (semi-batch cracking furnace) at an operating temperature and heating rate of 500 °C and 10 °C/min under inert atmosphere (N2 ). Under optimized operating conditions, the LDH-loaded DS provided a bio-oil yield between 65 and 67 wt%, while the pyrolysis–gas yield was about 20 wt%. The FT-IR analysis of LDH-derived bio-oil confirmed the presence of aliphatic and aromatic hydrocarbons that can be used effectively for energy applications. The pyrolysis kinetics, pyrolysis gas composition, and thermodynamic properties of biomass-loaded with LDH were also investigated. Thermokinetic analysis was performed using data from Coats-Redfern, which fitted the kinetic model at five different reaction mechanisms: chemical reaction order, phase interfacial reaction, power-law, diffusion-controlled, and nucleation and growth models for biomass conversion rates of 20–40% and 40–80%. The results showed that the diffusion-controlled parabolic law (D1) and the fourth-order reaction model (F4) are likely mechanisms in the conversion range of 20–40% and 40–80% for LDH-loaded date seeds. Based on the ascending order of activation energy (Ea), the biomasses can be classified as DS > MF-DS > NF-DS > CF-DS. In addition, the main gasses released and detected from the decomposition of pure biomass (date seeds) and LDH-loaded biomass through a micro GC-Varian were CH4, H2, CO, and CO2 . A plausible reaction mechanism for the role of layered double hydroxides in the conversion of bio-oils and pyrolytic-gas components was also presented. This study demonstrates the role of LDH-based catalysts in the pyrolysis of date seeds to produce value-added chemicals and biofuels.